Quality Program Life Cycle Sebagai Model Diklat Pengembangan Pemberdayaan Masyarakat Berbasis Riset - Romanda Annas Amrullah; Budi Joko Raharjo; Yovananda Bayudewa Kusumawardhana (Majalah Ilmiah Bahari Jogja, 2021)
Skill-based vocational education and traning play a key role in promoting competitiveness and economic prosperity. However, in Indonesia as a country that has a demographic dividend and a maritime country has not become a priority for developing strong human resources to manage the wealth of the marine area, this is reflected in the vocational curiiculum that has never been reconstructed following changes int the external environment. This type of research is a hournal research with a qualitative explanation method. Intergrate finnish education and traning quality model conceptual theory, student choice theory to determine higher education choice and European maritime life cycle education and training model concept theory. The research resulted in the concept of a novelty model of the Quality Program Life Cycle Quality Program Life Cycle is a vocational education model tha prioritizes quality (recruitment, educatiob, training and mentoring) in a quality manner (cadets, lecturers, employees / staff, training) with a program that is measurable, transparent and accountable with full involvement of institutions, students and companies as a cycle (Life Cycle) in a sustainable manner. The explanation of dimensions, conceots, operations is further explained in this study.